Comparison of transpiration rate and stomatal and leaf features in black pepper (Piper nigrum L.), clove (Syzygium aromaticum (L) Merr and Perry), cinnamon (Cinnamonum zeylanicum Blume) and nutmeg (Myristica fragrans Houtt) - De Guzman, Constancio C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1992)
A comparative study of transpiration rate and stomatal and leaf features was made on the following spices: black pepper (Piper nigrum L.), clove (Syzygium aromaticum (L.) Merr and Perry), cinnamon (Cinnamonum zeylanicum Blume), and nutmeg (Myristica fragrans Houtt). Black pepper exhibited the highest rate of transpiration, followed in decreasing rate by clove, cinnamon and nutmeg. Values of stomatal density did not parallel the trend observed in transpiration rates, black pepper exhibiting one of the lowest, and cinnamon the highest stomatal density. Stomatal pore length was shortest in clove and longest in cinnamon while intermediate values were obtained for nutmeg and black pepper. Among the leaf parameters measured, only specific leaf area showed some positive bearing with transpiration rate. Scanning electron micrographs revealed detailed stomata and leaf surface features which could possibly account for the variation in transpiration rates of the four spices.